The frequency of SLCO1B1*5 polymorphism genotypes among Russian and Sakha (Yakutia) patients with hypercholesterolemia - Sychev DA; Shuev GN; Chertovskih JV; Maksimova NR; Grachev AV; Syrkova OA (Dove Medical Press, 2016)
Dmitrij Alekseevitch Sychev,1 Grigorij Nikolaevich Shuev,2 Jana Valer'evna Chertovskih,3 Nadezhda Romanovna Maksimova,3 Andrej Vladimirovich Grachev,1 Ol'ga Aleksandrovna Syrkova2 1Department of Internal Medicine and Clinical Pharmacology, Russian Medical Academy of Postgraduate Education, Moscow, 2Faculty of Postgraduate Education, Far Eastern State Medical University, Khabarovsk, 3Genetic Laboratory, Ammosov North-Eastern Federal University, Yakutsk, Russian Federation Introduction: Statins are the most commonly prescribed medicines for treatment of hypercholesterolemia. At the same time, up to 25% of patients cannot tolerate or have to discontinue the statin therapy due to statin-induced myopathy. In a majority of cases, statin-induced myopathy is attributed to SLCO1B1 gene polymorphism. The strongest association between statin-induced myopathy and SLCO1B1 gene polymorphism was described for simvastatin. Our research was focused on the frequency of SLCO1B1*5 genetic variant in the Russian population and in the native population of Sakha (Yakutia).Materials and methods: A total of 1,071 hyperlipidemic Russian and 76 hyperlipidemic Sakha (Yakutian) patients were included in the study. Genotypes of SLCO1B1*5 (c.521T>C, rs4149056) were determined with polymerase chain reaction amplification. The results of our study were compared with data about hyperlipidemic patients in available publications.Results: In the Russian population 665 (62%) patients had TT genotype of SLCO1B1*5, 346 (32%) patients had TC genotype, and in 60 patients (6%) CC variant was found (Hardy–Weinberg's chi-square test was 3.1 P=0.21). In comparison with Brazil, France, the People's Republic of China, Japan, and the native population of Sakha (Yakutia), C-allele, which causes an increased risk of statin-induced myopathy, was found significantly more often in the Russian population. In the native population of Sakha (Yakutia) SLCO1B1 polymorphism was TT – 62 (82%), TC – 11 (14%), CC – 3 (4%) (Hardy–Weinberg's chi-square test was 5.13 P=0.077). In comparison with data from Brazil, France, the People's Republic of China, and Japan, C-allele frequency in the Sakha (Yakutian) population was not significantly different.Conclusion: Thus, we have studied the incidence of pathologic SLCO1B1 c.521C-allele in Russian and Sakha hyperlipidemic patients. The presence of SLCO1B1 C-allele in patients with hyperlipidemia forces us to be more careful in hypolipidemic drug prescription, especially statins, according to a higher risk of statin-induced myopathy development. The fact that SLCO1B1 C-allele is rarer among Sakha patients, could be interesting from the point of studying adverse drug effects frequency and statins' effectiveness.Keywords: Russian, Sakha (Yakutia), pharmacogenetics, SLCO1B1, statins, myopathy